FACTORS ASSOCIATED WITH LENGTH OF STAY AMONG HEALTH INSURANCE PARTICIPANTS: A CASE STUDY AT INSURANCE COMPANY X IN 2025 - Senintyas Fresitinawati; I Made Indra P; Salim Al Bakry (Yayasan Education and Social Center, 2026)
Length of stay (LOS) is an important indicator of inpatient service utilization and claim efficiency in health insurance management. This study aims to analyze factors associated with LOS among health insurance participants at Insurance Company X in 2025. This research used a quantitative, non-experimental approach with a cross-sectional design and secondary data obtained from inpatient claim and membership records. A total of 499 inpatient cases were analyzed. The independent variables included gender, age, membership status, hospital type, and disease diagnosis category, while the dependent variable was LOS. Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test. The results showed that gender was significantly associated with LOS (p = 0.034). Hospital type and disease diagnosis category were also significantly associated with LOS (p < 0.001). However, age (p = 0.404) and membership status (p = 0.783) were not significantly associated with LOS. These findings indicate that clinical and service-related factors are more relevant in explaining LOS variation than demographic or membership characteristics. The study provides practical insight for claim monitoring and inpatient utilization management in health insurance.